2017
DOI: 10.3389/fphys.2017.00637
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Strength and Sprint Levels, and Changes in Blood Parameters during a Complete Athletics Season in 800 m High-Level Athletes

Abstract: The purpose of this study was to analyze changes in sprint, strength, hematological, and hormonal parameters in high-level 800 m athletes during a complete athletics season. Thirteen male athletes of national and international level in 800 m (personal best ranging from 1:43 to 1:58 min:ss) participated in this study. A total of 5 tests were conducted during a complete athletics season. Athletes performed sprint tests (20 and 200 m), countermovement jump (CMJ), jump squat (JS), and full squat (SQ) tests. Blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 70 publications
(97 reference statements)
2
24
1
1
Order By: Relevance
“…Compromised immune function is a well-documented component of "overtraining syndrome" in elite athletes (30,75,87). Large workloads of high-intensity exercise are associated with reduced white blood cell count, including reduced neutrophils, monocytes, and lymphocytes (T cells) (6,51,75).…”
Section: Immune Systemmentioning
confidence: 99%
“…Compromised immune function is a well-documented component of "overtraining syndrome" in elite athletes (30,75,87). Large workloads of high-intensity exercise are associated with reduced white blood cell count, including reduced neutrophils, monocytes, and lymphocytes (T cells) (6,51,75).…”
Section: Immune Systemmentioning
confidence: 99%
“…However, we determined that the values for the other sub-parameters taken before and after the preparation period were statistically nonsignificant. In a research study conducted on national and international level 13 male 800 m runners, comparing the summer and winter competition periods, it was determined that there were decreases for the RBC values and also statistically significant decreases for the HCT values [2]. It was reported that short term intensive basketball competition caused a statistically significant decrease for the HCT parameters of the athletes, while causing a statistically non-significant decrease for RBC and HGB parameters [3].…”
Section: Discussionmentioning
confidence: 99%
“…When we examined the thrombocyte and its subparameters, compared to the values obtained before the preparation period, we observed that there were decreases in all parameters of both male and female taekwondo athletes, except for the PLT value of the female taekwondo athletes. As far as the accessible literature findings, although there are many research studies [12,15,16,21,24,[26][27][28] reporting that both acute and chronic exercises cause increases in the values of thrombocyte and its sub-parameters, there are also studies [2,3,18] reporting that they cause a decrease. Increases obtained in the PLT levels are attributed to both exercise-contingent hemoconcentration and sympathetic nervous system activation, which is caused by stress-creating factors and the organism under pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations